Improving Students’ Reading Comprehension of Narrative Text Using Folklore at SMK Negeri 9 Kabupaten Tangerang (A Classroom Action Research) - Fidiatun Adiyan; Vicky Hidantikarnillah; Ixnes Ayu Sarwendah (JURNAL PENDIDIKAN DAN SAINS, 2022)
Abstract - The objective of this research is to find out whether or not teaching reading through CAR using folklore can improve the reading comprehension of narrative text on the first grade students of SMK Negeri 9 Kabupaten Tangerang. The writer conducted the learning process in reading through folklore by Classroom Action Research. It focused on Kurt Lewins’ Design: Planning, Acting, Observing, and Reflecting. The instruments that were used in this research involved the English test sheet, observation sheets, and interview guidelines. For collecting the data, the writer gave the test in the form of narrative text, and the students had to answer the essay questions based on the text that they had learned before. Based on the research result, the comprehension of students in learning the text through folklore has improved. The result of pre-test, there are only 4 students who passed the KKM. The result of post-test in the second cycle gained 20 students who passed the KKM and derived mean score 80,75. In addition, students’ responses to learning are generally positive. Based on these findings, it can be concluded that the use of jigsaw technique can improve students’ reading comprehension of narrative text on the first grade students of SMK Negeri 9 Kabupaten Tangerang. Keywords: Reading Comprehension, Folklore, Narrative Text, A Classroom Action Research.